Native Yemeni Plumbago auriculata as a Promising Antioxidant and Antifungal Plant against Different Fusarium species - Al-Deen, Aziza Taj; Al-Jobory, Hala J (PSM Biological Research, 2018)
Plants and plant derived metabolites are believed as rich source of antifungal and antioxidant agents, with their fewer side effects, they are finding their way into pharmaceutical derivatives. The present study was undertaken to investigate the methanolic leaves and flowers extracts of Plumbago auriculata for their potential activity against phytopathogens and antioxidant efficiency. The extracts were evaluated against different pathogenic Fusarium species; F. verticilloides, F. oxysporum and F. solani using agar well diffusion method. F. oxysporum showed the higher susceptibility of inhibition with all extracts, followed by F. solani and F. verticilloides in case of leaves extracts, while F. verticilloides was the most sensitive after F. oxysporum in case of flowers extracts. It was clear that 75% concentration was the most effective among all concentrations tested. In DPPH (free radical scavenging assay) for antioxidant evaluation for the plant extract. The flowers extracts showed higher antioxidant activity than those of leaves with a dose-dependent manner. This study support the use of this herbal plant as antioxidant and antifungal agent to control Fusarium species especially F. oxysporum the causative agent of Fusarium wilt of tomato.